Visualising student finances: A data-driven approach / Nur Hasni Nasrudin ... [et al.] - Nasrudin, Nur Hasni; Mohd Zuber, Muhammad Adam Emir; Ahmad, Samsiah; Azmi, Anis Zafirah; Ahmad Junid, Rosida (2024)
This project employs data visualization techniques to aid university students in managing their finances effectively, addressing prevalent challenges such as financial stress and poor decision-making stemming from a lack of resources and personalized planning tools. Through intuitive visualization, the app simplifies complex financial data, empowering students to make informed choices. Following the Waterfall Model, the project progresses through planning, designing, developing, testing, and deploying phases. Its significance lies in enhancing financial management skills, alleviating stress, and fostering healthy financial habits among students. By tailoring a personalized tool, the research contributes to financial planning, aiming to meet the unique needs and objectives of university students. An experiment done with a sample size of 30 students demonstrates favorable responses, validating the efficacy of the selected visualization methods. However, limitations include reliance on Android and internet access, and targeting solely university students. Future enhancements entail expanding to iOS for broader accessibility and integrating artificial intelligence for expense forecasting, aiming to accommodate diverse user demographics.